1996
DOI: 10.1364/ao.35.005925
|View full text |Cite
|
Sign up to set email alerts
|

Mode-volume and pump-power limitations in injection-locked TEM_00 Nd:YAG rod lasers

Abstract: Stress-induced birefringence in cw-pumped Nd:YAG rods create stability limitations on the TEM(00) polarized mode of a resonant cavity. We present and verify experimentally a thermo-optical model describing a ring cavity containing a birefringent cw-pumped Nd:YAG rod. We use the model, along with experimental evidence, to show that a fundamental TEM(00) mode size and pump-power limitation exists for any cw-pumped Nd:YAG laser, implying a maximum allowable TEM(00) output. We show that the largest TEM(00) mode ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
4

Year Published

2000
2000
2014
2014

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(16 citation statements)
references
References 14 publications
0
12
0
4
Order By: Relevance
“…Because of this, each polarization is equally focused on the output coupler and Y-leg side of the rod, and the rand φ-polarization modes overlap perfectly. An ABCD matrix analysis is used to model the cavity [5] including the thermo-optic properties of the Nd:YAG rod. This model enables study of the laser mode and stability criteria as it propagates through the cavity.…”
Section: Methodsmentioning
confidence: 99%
“…Because of this, each polarization is equally focused on the output coupler and Y-leg side of the rod, and the rand φ-polarization modes overlap perfectly. An ABCD matrix analysis is used to model the cavity [5] including the thermo-optic properties of the Nd:YAG rod. This model enables study of the laser mode and stability criteria as it propagates through the cavity.…”
Section: Methodsmentioning
confidence: 99%
“…However, in single rod lasers such as the one shown in Fig. 1, stress-induced birefringence and bifocusing place a limit on the TEM 0,0 mode size that can be produced 15 .…”
Section: Dual Rod Yb:yag Laser Performancementioning
confidence: 99%
“…Therefore, the depolarization as a result of the thermally induced birefringence becomes the limiting effect on power scaling. Especially in rod lasers Knoke and Murdough et al [3,4] demonstrated that the linearly polarized output power of a single rod system is limited to a maximum of 45 W due to depolarization. To overcome this limit and to scale a rod laser design into the high power range, a double rod concept combined with a 90 degree quartz rotator is used to compensate the thermally induced birefringence [5,6].…”
Section: Introductionmentioning
confidence: 99%